the ancient poetic critical term between Osama bin Munqith and Musa bin Ezra: A Contrastivecomparative study Literary metaphor and literary repetition model” (مجلة إحالات, 2026)
This study, tagged with -"the ancient poetic critical term between Osama bin Munqith and Musa binEzra: A Contrastive comparative study Literary metaphor and literary repetition model”-, the terminology of ancient poetic criticism in two books by authors of two different religions. to discuss their personal opinions in the terminology of ancient poetic criticism. The study used the analytical and contrastive method; By explaining the views of each of them, the study reached a number of results, including , Hebrew endeavors to copy the ancient Arab criticism to advance the Hebrew poetry, but it has not been able todevelop at the Arab monetary level.